Pengaruh Pengalaman Terhadap Kepuasan dan Niat Berkunjung Kembali Wisatawan Nusantara Pada Masa Pandemi di Taman Nasional Baluran - Martalia, Diana; Sudiarta, I Nyoman; Mananda, I GPB. Sasrawan (Jurnal Master Pariwisata (JUMPA), 2022)
The experience of domestic tourists during the pandemic can affect their satisfaction and intention to revisit Baluran National Park. This is because domestic tourists during the pandemic need destinations that are safe from Covid-19. The aims of this study were: (1) to determine the effect of the domestic tourist experience on satisfaction; (2) to determine the effect of satisfaction on the intention to revisit; (3) to determine the effect of domestic tourist’s experience on the intention to revisit; and (4) to determine the effect of the dosmestic tourist’s experience on the intention to revisit through satisfaction as a mediating variable. This research was conducted in Baluran National Park, East Java, from February to March 2022. The sample used was a random sample with 160 respondents, namely domestic tourists. The data were analyzed using a quantitative approach with the PLS-SEM method, strengthened by qualitative data from observations and interviews. The results showed that: (1) experience affects satisfaction; (2) satisfaction affects the intention to revisit; (3) experience has not affected the intention to revisit; and (4) experience influences the intention to revisit through satisfaction as a mediating variable. Keywords: experience, domestic tourists, satisfaction, intention to revisit, pandemic period, Baluran National Park.